Enhancing Learning and Assessment Management through Microsoft Teams Training at MA Nurul Qadim - Iman, Dian Zulfatul; Arifin, Misbahul; Hasanah, Siti Waqi’atul; Dayem, Fatimah Gamal Abdel (LPPM STAI Darul Falah, 2026)
The rapid digital transformation in education has redefined teaching and assessment practices, demanding teachers to strengthen their competence in managing technology-based learning environments. This community service project aimed to enhance the digital capacity of teachers at MA Nurul Qadim by implementing Microsoft Teams as a central platform for instruction, collaboration, and assessment. The program employed a combination of applied training, participatory practice, and continuous mentoring to build teachers’ digital literacy and pedagogical adaptability. Through hands-on workshops, teachers learned to create virtual classrooms, organize learning materials, conduct interactive sessions, and manage student assessment within the platform. Evaluation results, drawn from pre- and post-training assessments, classroom observations, and reflective interviews, revealed a significant increase in teachers’ digital competence and confidence in using Microsoft Teams for instructional purposes. Moreover, the initiative produced Standard Operating Procedures (SOPs) to ensure consistent and sustainable digital practices across the institution. Overall, the project underscores that contextually grounded and structured professional development can effectively foster teachers’ technological proficiency, encourage innovation in pedagogical approaches, and build a resilient school culture that is responsive to ongoing educational transformation.